The Threat of Narcotics and Social Value Transformation to Indonesia's National Resilience: A Non-Traditional Security Perspective - Firmansyah; Maisondra; Edwin (Arus Jurnal Sosial dan Humaniora, 2026)
The dynamics of globalization have transformed the nature of threats faced by nation-states. Security is no longer limited to military aggression but increasingly encompasses non-traditional threats such as narcotics trafficking, transnational organized crime, and social value transformation. This study aims to analyze the impact of narcotics abuse and social value changes on Indonesia's national resilience from a non-traditional security perspective. Using a qualitative approach and literature review method, this study examines theories of national resilience, human security, and non-traditional security. The findings indicate that narcotics abuse has multidimensional impacts on public health, economic productivity, social stability, and governance. Meanwhile, rapid social value transformation driven by globalization and digitalization has generated challenges for social cohesion and national identity. The combination of these threats may weaken national resilience if not addressed through comprehensive governance involving government institutions, educational sectors, communities, and families. The study recommends strengthening preventive policies, civic education, family resilience, and integrated national security strategies to address emerging non-traditional threats.